PEMANFAATAN LIMBAH SERABUT KELAPA MUDA SEBAGAI ELEKTRODA KARBON SUPERKAPASITOR DENGAN VARIASI KONSENTRASI AKTIVATOR ZnCl2 - Ridho Nopriansyah; Awitdrus Awitdrus (Indonesian Physics Communication, 2023)
The chemical activation method is a simple and low-cost activation method that can modify the surface morphology associated with improving the electrochemical properties of supercapacitor cell electrodes. The porous carbon framework was derived from young coconut fiber biomass by optimizing the chemical activation reagent (ZnCl2). Carbon material derived from coconut fiber is a biomass for the application of supercapacitor cell electrodes through the pre-carbonization stage at 200°C for 1 hour 30 minutes, chemical activation using the activating agent ZnCl2 with various concentrations of 0.1, 0.3, and 0.5 M, the carbonization process uses gas N2 with a temperature of 600°C and physical activation using CO2 gas with a temperature of 750°C. The optimum concentration of young coconut fiber-based carbon electrodes is found at a concentration of 0.5 M, which has the highest density shrinkage percentage of 53.11%. X-ray diffraction analysis showed that the sample at a concentration of 0.5 M was amorphous with two wider diffraction angle of 2q at an angle of 24.867° and 44.556°, with the lowest Lc/La ratio of 0.3 and an average microcrystalline layer of 2.3. Analysis of electrochemical properties showed that samples at a concentration of 0.5 M has an optimum specific capacitance of 81.84 F/g in the CV.